2012
DOI: 10.5303/pkas.2012.27.3.095
|View full text |Cite
|
Sign up to set email alerts
|

THE STATUS AND IMPROVEMENT PLAN OF 1.8 m TELESCOPE CONTROL SYSTEM AT BOAO

Abstract: We analyzed the current status of the telescope control system (TCS2) of the 1.8 m telescope in Bohyunsan Optical Astronomy Observatory (BOAO), and suggest a new TCS (TCS3) for the long term development of BOAO. The TCS2 was constructed in 1998 to replace the TCS1 which was installed with the telescope itself at the commencement of BOAO. One of the important parts of TCS is PMAC (Programmable Multi-Axis Controller), which is a general-purpose multi-axis motion controller. PMAC provides the direct interactive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
1
0
1
Order By: Relevance
“…국내 최초로 소백산천문대에 CCD 카메라가 도입된 1990년대 초에는 25만 픽셀 (Park 1993;Kim et al, 1993)에 불과했었는데, 보현산천문대 1.8 m 망원경 이 설치된 1990년대 중반에는 1백만 픽셀의 1k CCD 카메라 (Park et al, 1995)를 사용하다가, 2000년대에는 4 백만 픽셀의 2k CCD 카메라 (Park et al, 2001;Kim et al, 2001)로 변경되었고, 2010년대에는 16백만 픽셀을 가진 4k CCD 카메라 (Sung et al, 2012) (Freyhammer et al, 2001). Victim 5b 또는 Source 2a와 Victim 6a 등에서 나타나는 …”
unclassified
“…국내 최초로 소백산천문대에 CCD 카메라가 도입된 1990년대 초에는 25만 픽셀 (Park 1993;Kim et al, 1993)에 불과했었는데, 보현산천문대 1.8 m 망원경 이 설치된 1990년대 중반에는 1백만 픽셀의 1k CCD 카메라 (Park et al, 1995)를 사용하다가, 2000년대에는 4 백만 픽셀의 2k CCD 카메라 (Park et al, 2001;Kim et al, 2001)로 변경되었고, 2010년대에는 16백만 픽셀을 가진 4k CCD 카메라 (Sung et al, 2012) (Freyhammer et al, 2001). Victim 5b 또는 Source 2a와 Victim 6a 등에서 나타나는 …”
unclassified
“…Jeong et al (1999) and Yoon et al (2006) developed auto-guiding systems for improving the tracking accuracy of the telescope in the Seoul National University and Chungbuk National University observatory, respectively. Sung et al (2012) suggested a new TCS to improve the tracking accuracy of the 1.8-m telescope at the Bohyunsan Optical Astron-omy Observatory. Kanzawa et al (2006) and Iseki et al (2008) made an effort to improve the accuracy of pointing and guiding of Subaru Telescope.…”
Section: Introductionmentioning
confidence: 99%